2016
DOI: 10.1371/journal.pone.0158309
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Year Randomized Trial of Interventions to Decrease Stress Hormone Vasopressin Production in Patients with Meniere’s Disease—A Pilot Study

Abstract: Meniere's disease, a common inner ear condition, has an incidence of 15–50 per 100,000. Because mental/physical stress and subsequent increase in the stress hormone vasopressin supposedly trigger Meniere's disease, we set a pilot study to seek new therapeutic interventions, namely management of vasopressin secretion, to treat this disease. We enrolled 297 definite Meniere's patients from 2010 to 2012 in a randomized-controlled and open-label trial, assigning Group-I (control) traditional oral medication, Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 39 publications
0
39
0
Order By: Relevance
“…Six studies were non-industry funded [ 35 , 36 , 38 , 39 , 41 , 47 ], five declared no funding [ 40 , 42 44 , 57 ], and seven did not report funding source [ 37 , 45 , 46 , 48 – 51 ]. Country of conduct and/or the corresponding authors’ locations varied across the studies, and included the United States [ 35 ], Canada [ 57 ], Brazil [ 45 ], Egypt [ 51 ], Germany [ 41 ], India [ 37 ], Iran [ 36 ], Italy [ 44 ], Italy and Romania [ 40 , 42 ], Japan [ 39 , 47 ], Mexico [ 48 , 49 ], the Netherlands [ 43 , 46 , 50 ], and the United Kingdom [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies were non-industry funded [ 35 , 36 , 38 , 39 , 41 , 47 ], five declared no funding [ 40 , 42 44 , 57 ], and seven did not report funding source [ 37 , 45 , 46 , 48 – 51 ]. Country of conduct and/or the corresponding authors’ locations varied across the studies, and included the United States [ 35 ], Canada [ 57 ], Brazil [ 45 ], Egypt [ 51 ], Germany [ 41 ], India [ 37 ], Iran [ 36 ], Italy [ 44 ], Italy and Romania [ 40 , 42 ], Japan [ 39 , 47 ], Mexico [ 48 , 49 ], the Netherlands [ 43 , 46 , 50 ], and the United Kingdom [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Findings, tympanic ventilation + oral medication (including diuretics, betahistine, diphenidol, dimenhydrinate, and diazepam) versus the same oral medication alone. One trial [39] demonstrated a statistically significant difference favoring tympanic ventilation combined with oral medication against the same medication alone for complete vertigo control (RR 1.55, 95% CI 1.22 to 1.97; n = 133) demonstrated in SA7 Fig. Findings, IT steroid versus low-dose Betahistine + cinnarizine + diet restrictions. There was no difference between IT steroid (dexamethasone) and conventional therapy comprising of salt and caffeine-restricted diet, nicotine and alcohol restrictions, cinnarizine (75 mg/day) for acute episodes and low-dose betahistine (48 mg/day) for maintenance therapy in terms of excellent and good vertigo control measured based on Sakata's criteria [58] (RR 1.13, 95% CI 0.55 to 2.32; n = 40) based on a single trial [37] demonstrated in SA7 Fig in S4 Text.…”
Section: Plos Onementioning
confidence: 99%
“…). The remaining 88 patients with intractable idiopathic BPPV were randomly assigned through computer‐generated block randomization organized by the clinical study section at Nara Medical University Hospital to one of the two treatment groups . Patients received head‐position management when lying down at home and continuous medication with antivertigo and antinausea drugs as needed.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, VTI has been proposed to modify the vasopressin-secretion from the hypothalamic-pituitary system mediated by vestibulo-hypothalamic neural interactions. 27 Final Comments There are no RCTs that directly assess the efficacy of VTI on the number of vertiginous attacks in patients with definite or probable MD. Current data are suggestive of a considerable positive effect on the number of vertiginous attacks in patients with MD.…”
Section: International Archives Of Otorhinolaryngologymentioning
confidence: 99%